How Students’ Perspectives about Online Learning Amid the COVID-19 Pandemic? - Della Shinta Bestiantono; Putri Zulaiha Ria Agustina; Tsung-Hui Cheng (Indonesia Approach Education, 2020)
This exploration study inspects the perspectives of Indonesian junior high school students towards learning courses amid Coronavirus (COVID-19). Secondary students were overviewed to discover their viewpoints about online training in Indonesia. The discoveries of the investigation featured that web-based learning cannot create wanted outcomes in immature nations like Indonesia, where a larger part of understudies cannot get to the web because of specialized just as money-related issues. The absence of eye-to-eye connection with the educator, reaction time and nonattendance of conventional homeroom socialization were among some different issues featured by advanced education understudies.